Aanguilla_olfactory_expression_data - Churcher, Allison M.; Hubbard, Peter C.; Marques, João P.; Canário, Adelino V. M.; Huertas, Mar (Dryad Digital Repository, 2015)
These are the expression data for the olfactory epithelium of freshwater (FW), seawater (SW) and sexually mature (SM) male A. anguilla. The expression values are condition means and the protein descriptions for the transcriptome assembly contigs are based on a BLAST search of RefSeq proteins. For further details, please see the associated publication